Challenges and coping startegies among informal stroke survivor caregivers - Johar, Norulmumtazah (2019)
Most of stroke survivor caregiver need to full fill their activity daily living including stroke survivor needs. Informal stroke caregiver usually came from family. Caregivers of stroke survivor required a time for adaptation and adjustment in their life. Most of the qualitative study had found, majority of the informal stroke survivor caregiver facing increased responsibilities, new roles and physical changes due to caregiving of stroke survivor. They also need a training to deal with the stroke survivor disability which need long time in caregiving and this time consuming activities can affect caregivers social activities. This study is phenomenology qualitative study, using purposive and maximum variation sampling. Data were obtained using semi structured open-ended question via interview session. Thematic analysis was used to assess the experiences of informal stroke caregivers. This study provided 20 participants of informal stroke caregivers which are over a period of 6 months post discharge from hospitalization. Three major themes were found in this study. (1) Challenges in caring stroke survivor (2) Limited available support in caregiving. (3) Caregivers coping strategies. This study concludes that informal stroke caregivers used more time and energy in order to manage stroke survivor.